THE EFFECT OF EASE OF DOING BUSINESS (EODB) AND CORRUPTION PERCEPTIONS INDEX (CPI) ON FOREIGN DIRECT INVESTMENT (FDI) IN ASEAN - Firdaus, Firdaus; Fakhruddin, Imam; Fitradinata, Kheqal; Hidayat, Riyan (Finansha: Journal of Sharia Financial Management, 2024)
The background of this study is the instability of foreign investment in Southeast Asia due to declining corporate revenues and the Covid-19 pandemic, which has caused economic uncertainty and delayed investments by multinational companies. This study aims to examine the influence of the Ease of Doing Business (EoDB) and the Corruption Perception Index (CPI) on Foreign Direct Investment (FDI) in ASEAN. The research employs Structural Equation Modeling using Partial Least Square (SEM-PLS 4) software. The population in this study includes all countries in the Southeast Asian region, with a total sampling or census approach. The results indicate that the Ease of Doing Business does not affect Foreign Direct Investment. This is largely due to the low EoDB index scores in most ASEAN countries. In contrast, the Corruption Perception Index has a positive and significant effect on Foreign Direct Investment, suggesting that foreign investors have greater confidence to invest and feel that their substantial funds will be safer. The implications of this study suggest that ASEAN governments must enhance the investment climate by implementing regulatory reforms that promote the Ease of Doing Business and reduce corruption levels. These efforts are expected to improve regional competitiveness and attract more foreign investment, ultimately accelerating economic growth and infrastructure development in the region.